Ukrainian botanical, acclimatization gardens and dendroparks – centers of introduction of Rosa L. representatives - O.L. Rubtsova (Інтродукція Рослин, 2006)
On the base of literary data and own long-time researches the analysis of activity of Ukrainian botanical, acclimatization gardens and dendroparks in introduction and creation roses' genofund are given.